On the track of anthropogenic activity in carnivore dens: altered combustion structures in Cova del Gegant (NE Iberian Peninsula) - Sanz, Montserrat (2018)
Cova del Gegant (Barcelona, NE Iberian Peninsula) is a Middle Palaeolithic site presenting evidence of carnivore occupations with some sporadic Neanderthal activity. The rapid, fine sedimentation in layer IIIa permitted the preservation of the remains of carnivore activity and an ephemeral combustion area, although lithics are absent. We used a detailed excavation procedure in combination with Fourier transformed infrared spectroscopy, soil micromorphological, zooarchaeological and taphonomical analyses, and coprogenic analysis to evaluate the interactions of humans and carnivores in the same area of the cave.